Seedling emergence of the Lulo (Solanum quitoense Lam.) in storage time function - Amaral, Uira do; Carvalho, Silvio Luis de; Silva, Isabella Borges; Santos, Valdineia Maria dos; Santos, Miqueias Gomes dos [UNESP] (Federal Inst Amapa, Campus Macapa-ifap, 2016)
The Lulo (Solanum quitoense Lam.), belongs to the Solanaceae family originates from Andean regions, generally the fruits produces about 1.000 seeds and the sexual propagation the main form of propagation of the species. This study aimed to evaluate the influence of storage time in the emergency Lulo seeds from three harvest seasons. The experiment was conducted in a completely randomized design with three treatments (three months, six months and twelve months) and seven replications. The seeds were sown in polystyrene trays of 128 cells in commercial substrate Bioflora (R). It was observed that the physiological quality of seeds lobe decreased significantly when stored in paper sacks at room temperature for a period exceeding six months. However, there was no significant difference between treatments on the variable average time of emergency. The variables presented the highest averages for seeds stored for three months, especially for emergency approximately 70%.
Keywords: Seed physiology; exotic fruits; small fruits